Management of labyrinthine fistula using Surdille flap - Rajashekhar, Rashmi P.; Shinde, Vinod V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Labyrinthine fistula (LF) is the most common intra-temporal complication of squamosal chronic otitis media represents an erosive loss of endochondral bone overlying the semicircular canals without loss of perilymph. Main treatment of LF is surgical. The aim of our study is to discuss its incidence and sex ratio. The main objective is to describe the audio-vestibular results after closure of labyrinthine fistula by our technique using surdille flap. Methods: 234 patients with squamosal chronic otitis media presented to our institution in a period of 24 months. Out of 234 patients, 22 patients were having labyrinthine fistula. Eleven patients had fistula test positive. Rest eleven patients were found to have LF intra-operatively. All patients underwent canal wall down modified radical mastoidectomy (MRM). Treatment of LF was done surgically by using surdille flap in all the cases. Post operatively Audio-vestibular results of labyrinthine fistula surgery by our technique were studied. Results: The results show that the cholesteatoma matrix can be removed from the fistula. Removal of the fistula generally improves the vestibular symptoms. In all patients canal wall down procedure was done with surdille flap seal over LF. In our study, incidence of LF was 9.40% and none of the patients ended up with postoperative deafness. Hearing improved in 36.40% patients whereas it remained unchanged in rest of the cases. Conclusions: Labyrinthine fistula, very commonly seen in the lateral semicircular canal has incidence of 5-10% reported in many studies. We demonstrated that open technique with removal of matrix and sealing with three layers may be a valuable choice for the surgical treatment of LF with little risk for cochlea-vestibular functions. Advantage of using surdille flap (sealing the fistula with three layers) is that it decreases the possibility of postoperative vertigo.